ANALISIS DETERMINAN ANTARA KEPUASAN KERJA DENGAN KINERJA PERAWAT (Studi Kasus BRSUD Kab. Batang) - Danang Satrio (Jurnal Ekonomi Dan Bisnis, 2015)
The hospital is a services company, where its products are produced intangible, and originate from the service providers which in this case is a clerk or we call HR. Job satisfaction nurse needs serious attention of the hospital management, because most nurses are employees and spearhead implementing nursing services. With the realization of job satisfaction of nurses is expected to create a better nursing care. Factors that influence job satisfaction in BRSUD Kab.Batang is a factor incentive compensation,leadership style and content of work, while work environment and promotion has no effect on job satisfaction Keywords: Job Satisfaction, Performance